2016
DOI: 10.1177/1359105316671187
|View full text |Cite
|
Sign up to set email alerts
|

Relationship cognitions and longitudinal trajectories of sexual risk behavior among young gay and bisexual men: The P18 cohort study

Abstract: This study examines how romantic relationship cognitions are associated with changes of condomless anal sex among emerging adult gay and bisexual men. The sample was drawn from 4-waves of a prospective cohort study (N = 598; Mage = 18.2). Results suggest that condomless anal sex increased over the emerging adulthood period. Romantic relationship fear was associated with increased receptive condomless anal sex. Perceptions of greater romantic relationship control increased the likelihood of having insertive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Our relational expectation factors build on extant literature such as romantic fear, romantic obsession, commitment, intimacy, and passion (Bauermeister et al, 2012; Bauermeister, 2012; Cook et al, 2018). Although some factors were renamed or dropped from our factor analysis, the factors found to be salient in our analysis are largely consistent with our hypothesized factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our relational expectation factors build on extant literature such as romantic fear, romantic obsession, commitment, intimacy, and passion (Bauermeister et al, 2012; Bauermeister, 2012; Cook et al, 2018). Although some factors were renamed or dropped from our factor analysis, the factors found to be salient in our analysis are largely consistent with our hypothesized factors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Cook et al (2018) found greater romantic fear about not being in a romantic relationship was positively associated with increased receptive condomless anal sex among YGBM, while greater perceived romantic control of relationship functioning was positively associated with both insertive and receptive condomless anal sex (Cook et al, 2018). These findings highlight the potential nuance of relational cognitions on YGBM's sexual decision-making and sexual health.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…(19) In the case of this study, young men with a more fragile look, more delicate physical features, or effeminate were considered inferior than men who followed prevalent standards of masculinity, rooted as one of the greatest "Latin heritage". (6,17) Seeking support from a reliable person, friend, or family is common to everyone who experiences situations of violence, since expressing feelings may be a way to face reality. However, support found by young homosexuals and bisexuals was fragile, because of the fear of disclosing aspects of their lives that could generate judgment.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers bring nuances in their studies, on the situations of violence in the lives of young people; however, without further deepening and leaving gaps on the association of violence with the vulnerability of young men who have sex with men. (3)(4)(5)(6)(7) Therefore, the following question emerges: "Does violence, in its different forms, make young homosexuals and bisexuals vulnerable to HIV/ Aids?" Therefore, the objective of the authors of the present study was to know the perceptions of young people who identify themselves as homosexuals or bisexuals on experienced violence and identify possible correlations with vulnerability to HIV/Aids.…”
Section: Introductionmentioning
confidence: 99%